Pharmacokinetics of Intraperitoneal Vancomycin and Amikacin in Automated Peritoneal Dialysis Patients With Peritonitis - Falbo dos Reis, Pâmela [UNESP]; Barretti, Pasqual [UNESP]; Marinho, Laudilene [UNESP]; Balbi, Andre Luís [UNESP]; Awdishu, Linda; Ponce, Daniela [UNESP] (Frontiers, 2021)
Objective: The study aimed to evaluate the vancomycin and amikacin concentrations in serum and dialysate for automatic peritoneal dialysis (APD) patients. Methods: A total of 558 serum and dialysate samples of 12 episodes of gram-positive and 18 episodes of gram-negative peritonitis were included to investigate the relationship between vancomycin and amikacin concentrations in serum and dialysate on the first and third days of treatment. Samples were analysed 30, 120 min, and 48 h after intraperitoneal administration of vancomycin in peritonitis caused by gram-positive agents and 30, 120 min, and 24 h after intraperitoneal administration of amikacin in peritonitis caused by gram-negative agents. Vancomycin was administered every 72 h and amikacin once a day. The target therapeutic concentration of amikacin was 25–35 mg/l at the peak moment and 4–8 mg/l at the trough moment; and after 48 h for vancomycin, 15–20 mg/l at the trough moment. Results: For peritonitis caused by gram-negative agents, at the peak moment, therapeutic levels of amikacin were reached in dialysate in 80.7% of patients with evolution to cure and in 50% of patients evaluated as non-cure (p = 0.05). At the trough moment, only 38% were in therapeutic concentrations in the dialysate in the cure group and 42.8% in the non-cure group (p = 1). Peak plasma concentrations were subtherapeutic in 98.4% of the samples in the cure group and in 100% of the non-cure group. At the trough moment, therapeutic concentrations were present in 74.4% of the cure group and 71.4% of the non-cure group (p = 1). Regarding vancomycin and among gram-positive agents, therapeutic levels were reached at the peak moment in 94% of the cure group and 6% of the non-cure group (p = 0.007). After 48 h, 56.8% of the cure group had a therapeutic serum concentration whereas for the non-cure group it was only 33.3% (p = 0.39). Conclusion: Despite a small sample size, we demonstrated peak dialysate amikacin level and peak serum vancomycin level correlates well with Gram-negative and Gram positve peritonitis cure, respectively. It is suggested to study the antibiotics pharmacodynamics for a better understanding of therapeutic success in a larger sample.
Keywords: amikacin; peritoneal dialiysis; peritonitis; pharmacokinetics; vancomicyn